Former Soviet Union middle class: How entrepreneurs are shaping a new stratum and pattern of socio-economic behavior - Elmira Otar; Rinat Salikzhanov; Aigul Akhmetova; Assel Issakhanova; Kuralay Mukhambetova (Journal of Innovation and Entrepreneurship, 2024)
The purpose of this study is to create a representative socio-economic profile of entrepreneurs operating in the former Soviet Union (FSU) states as a pillar of the new middle-class stratum. This study explored middle-class entrepreneurship from multiple perspectives, encompassing statistical analysis of microdata about households and firms. The aim was to gauge entrepreneurship within a national framework and examine its associations with social and economic factors. The study adopted the Doing Business tool as a novel paradigm to establish a quantitative correlation between the economic system in the post-Soviet space and the investigated variables. The analysis revealed that prospective entrepreneurs are members of the younger generation between the ages of 25 and 34; a critical factor in the development of entrepreneurship is highly educated human capital; and typical representatives of entrepreneurship intending to operate in the FSU states establish their own business as a means of subsistence, not as a means of advancement in the social stratum. In general, an entrepreneur of the middle class in the new economies of the post-Soviet space does not demonstrate a high level of entrepreneurial activity and, as a pillar of the middle-class stratum, is in the formation stage.
Keywords: 650; Business environment; Competitiveness; Economic development; Society; Transitional economy